A legitimidade ativa da Defensoria Pública para tutela dos direitos coletivos: suporte constitucional - Prado, Larissa Pilar (2012)
Conflicts of collective nature have gained space in modern society and therefore class actions have become a necessity of our times as they enable access to justice and allow the composition of legal disputes and ensure a more effective jurisdictional activity. In what concerns a broadening of the legitimacy and nonrestrainability of judicial appreciation, it has been granted infra-constitutional legitimacy to Public Defenders through the ope legis system adopted in Brazil, so that they can seek in Court protection of such public and collective rights. However, it is a controversial matter that of constitutional relevance of legal protection of such collective rights, and in relation to this it is argued that it would not pertain the Public Defenders prerogatives abilities other than assistance to the financial needy, and an economic analysis of the litigants would remain prejudiced in class actions. Fact is, regardless of the transfer of individual civil suits institutes to class actions, the latter has its own peculiarities and that alone requires different treatment. It is, furthermore, a powerful tool for facilitating access to justice for the aggrieved, which have difficulties due to the peculiar qualities of the involved parties and the collective nature of the dispute. On the other hand, as it will be shown, the Federal Constitution does not restrict the Public Defender prerogatives only to the institutional care of the financially needy given that there are many other difficulties and obstacles that must be overcome to ensure the access to justice, especially regarding collective rights. The interpretation of constitutional precepts must be in harmony with the guarantee system arranged by it. Hence, the constitutional rule that assigns the Public Defenders the protections of collective rights is perfectly approved and integrated with the constitutional text and context.